Understanding precipitation over the Southern Ocean through observations and high resolution simulations at Macquarie Island - Wang, Zhan (Monash University, 2017)
This thesis presents analyses of the historic surface precipitation and other relevant meteorological records observed at Macquarie Island (MAC). A basic climatology of the surface precipitation (frequency and intensity) is built and compared against a reanalysis model (ERA-I) and satellite products (CloudSat). The relationship between the precipitation and the synoptic meteorology is explored. The orographic effects of the island are studied by high-resolution numerical simulations. Macquarie Island (54.50 °S, 158.94 °E) is an isolated island with modest orography in the midst of the Southern Ocean with precipitation records dating back to 1948. These records are of particular interest due to the relatively large biases in the energy and water budgets commonly found in climate simulations and reanalysis products over the region. The surface precipitation is presented and compared against the ERA-I reanalysis. The annual ERA-I precipitation (953 mm) is found to underestimate the annual MAC precipitation (1023 mm) by 6.8 % from 1979 to 2011. The frequency of the 3-h surface precipitation (MAC) is 36.4 % from 2003 to 2011. Light precipitation (0.066 ≤ P < 0.5 mm hrˉ¹) dominates this precipitation (29.7 %), while the heavy precipitation (P ≥ 1.5 mm hrˉ¹) is rare (1.1 %). Drizzle (0 < P < 0.066 mm hrˉ¹) is commonly produced by ERA-I (43.9 %), but is weaker than the detectable threshold of MAC. Warm rain intensity and frequency from CloudSat products were compared with those from MAC. These CloudSat products also recorded considerable drizzle (under the detectable threshold of MAC) at frequencies of 16%-30%, but the frequencies were not significantly different than MAC when P ≥ 0.5 mm hrˉ¹. Heavy precipitation events were, in general, more commonly associated with fronts and cyclonic lows. Some heavy precipitation events were found to arise from weaker fronts and lows that were not adequately represented in the reanalysis products. Yet other heavy precipitation events were observed at points/times not associated with either fronts or cyclonic lows. Two case studies are employed to further examine this. High-resolution numerical simulations (Weather Research/Forecasting Model: WRF) with and without terrain have been used to identify orographic effects for four cases representing common synoptic patterns at Macquarie Island, namely a cold front, a warm front, post-frontal drizzle, and a mid-latitude cyclone. Results show that clouds and precipitation can readily be perturbed by the island with the main enhancement of precipitation normally in the lee in accordance with a large Froude number flow. Overall the orographic effect on the precipitation record is not found to be significant, except for the enhancement of drizzle found in southwesterly winds. Given the strong winds over the Southern Ocean and the shallow height of the island, the 3-D Froude number is found to be greater than one in most of the soundings (93.5%). Boundary layer flow commonly passes over the island with the greatest impact on the lee. For the 2-D cross wind flow, the frequency of the Froude number larger than one reduces to 83.7%.